Pancreatic cancer-associated gene polymorphisms in a nation-wide cohort of p16-Leiden germline mutation carriers; a case–control study - Potjer, Thomas P (BMC Res Notes, 2015)
BACKGROUND: The p16-Leiden founder mutation in the CDKN2A gene is the most common cause of Familial Atypical Multiple Mole Melanoma (FAMMM) syndrome in the Netherlands. Individuals with this mutation are at increased risk for developing melanoma of the skin, as well as pancreatic cancer. However, there is a notable interfamilial variability in the occurrence of pancreatic cancer among p16-Leiden families. We aimed to test whether previously identified genetic risk factors for pancreatic cancer modify the risk for pancreatic cancer in p16-Leiden germline mutation carriers. METHODS: Seven pancreatic cancer-associated SNPs were selected from the literature and were genotyped in a cohort of 185 p16-Leiden germline mutation carriers from 88 families, including 50 cases (median age 55 years) with pancreatic cancer and 135 controls (median age 64 years) without pancreatic cancer. Allelic odds ratios per SNP were calculated. RESULTS: No significant association with pancreatic cancer was found for any of the seven SNPs. CONCLUSIONS: Since genetic modifiers for developing melanoma have already been identified in CDKN2A mutation carriers, this study does not exclude that genetic modifiers do not play a role in the individual pancreatic cancer risk in this cohort of p16-Leiden germline mutation carriers. The search for these modifiers should therefore continue, because they can potentially facilitate more targeted pancreatic surveillance programs.